The Isoenergy Inequality for Harmonic Maps from Rotational Symmetric Manifolds (Journal of Partial Differential Equations, 2002)
Let u be a harmonic map from a rotational symmetric manifold M and B a unit ball in M, let E(u|B) be the energy of the map u|B and E(u|∂B) the energy of the map u|∂B, then we obtain the relationship which is called the isoenergy inequality between E(u|B) and E(u|∂B):